Análise De Discurso Crítica E Semiótica De Peirce: Uma Análise Interdisciplinar De Uma Capa Da Revista Carta Capital (PERcursos Linguísticos, 2022)
This article consists of an interdisciplinary analysis that aims to discuss the attribution of meanings of a cover of Carta Capital magazine. The general objective is to foster a discussion about the phenomena, signs, and discourses that constitute the magazine cover, in order to understand how the processes of sense construction take place. The theoretical basis is grounded on Semiotics studies, under the view of Peirce (2005) and Santaella (2005), in addition to Critical Discourse Analysis (CDA), according to the perspective of Fairclough (2001). The methodology is based on a descriptive, interpretative, and analytical perspective of the verbal and imagetic phenomena in the sign sphere, besides the discursive constructions that imply the choices of the signs under study. The results obtained are consistent with the hypothesis that the under-analysis cover of Carta Capital magazine brings discourses, which are socially motivated, consistent with the status of the magazine, and in line with the Brazilian political context of the time, since there are hegemonic discourses that probably seek in a consensual way to bring practices and actions to Brazil, especially in the electoral context for the 2018 year.